The Effect of Product Quality and Customer Satisfaction on Purchasing Decisions at Babang Redo Coffee Shop, Megamas Area, Manado - Keisya Tirsa Hermina Moningka; Hongky Dyrgo; Mercy R.H Mantur (Sean Institute, 2025)
This research aims to explore the influence of product quality and customer satisfaction on purchase decisions at Babang Redo Coffee Shop in Megamas Manado. The rapid growth of coffee shops in Manado has increased competition, making it essential for businesses to understand factors influencing consumer choices. This quantitative associative study collected data from 150 purposively sampled respondents via questionnaires. Data were analyzed using multiple linear regression with SPSS 25, including t-tests, F-tests, and coefficient of determination (R²). Results show that product quality and customer satisfaction significantly and positively affect purchase decisions both partially and simultaneously. The R² value of 0.729 indicates that 72.9% of purchase decision variance is explained by these variables, with customer satisfaction having a stronger effect. These findings suggest that continuous improvement in product quality and customer satisfaction directly strengthens consumer purchase decisions, providing a basis for effective marketing strategies.